Analgesic Activity of Bitter Melon Leaves Ethanol Extract in Mice (Mus musculus) - Nisa Najwa Rokhmah; Moerfiah Moerfiah; Hijib Sihabullah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Pain is an unpleasant sensation and can be felt as sore sensation. This can be caused by mechanical, chemical or physical stimulation that could cause damage to the tissueand trigger the release of certain substances called pain mediators, such as histamine, bradykinin, leukotrienes and prostaglandins. Pain overcome by giving analgesic drugs. This study aims to determine the effectivity and effective duration of bitter melon (Momordica charantia L.) leaf extract as analgesic in mice (Mus musculus). The test method used in this study is the Hot plate method. This study was divided into 5 treatment groups animals with 5 experimental animals in each group. Animal treatment of this study consist of a negative control group using CMC-Na (0.5%), a positive control group using Paracetamol, a suspension group of pare leaf ethanol extract with a dose of 0.212mg / 20gBW. , the ethanol extract suspension group of bitter melon leaves with a dose of 0.423mg / 20gBW, the suspension group of ethanol extract of pare leaves with a dose of 0.635mg / 20gBW. The results of this study indicate that the ethanol extract of 96% bitter melon leaves has activity as an analgesic in mice with the best dose of 0.635mg / 20gBW and the highest duration of analgesic activity was in 40 minutes, these activity was the closest result to positive control of paracetamol in mice.